COMPOUNDS PRODUCED BY ð˜Šð˜ð˜°ð˜¯ð˜°ð˜´ð˜µð˜¢ð˜¤ð˜©ð˜ºð˜´ ð˜³ð˜°ð˜´ð˜¦ð˜¢ DELETERIOUS TO ð˜‰ð˜°ð˜µð˜³ð˜ºð˜µð˜ªð˜´ ð˜¤ð˜ªð˜¯ð˜¦ð˜³ð˜¦ð˜¢ - Saraiva, Rodrigo Moreira; Borges, Ãlefe Vitorino; Borel, Filipe Constantino; Maffia, Luiz Antonio (REVISTA DE AGRICULTURA, 2020)
Clonostachys rosea is an antagonist to Botrytis cinerea, the causal agent of gray mold. It is known that C. rosea produces enzymes and secondary metabolism compounds deleterious to some pathogens, but its effect against B. cinerea has not been elucidated. In this paper, the activity of the compounds of C. rosea antagonistic to B. cinerea was assessed. We found that C. rosea does not produce volatile compounds that affect the pathogen. Compound(s) produced by the antagonist in culture medium inhibited the germination of conidia and the activities of sclerotia and mycelia. The effect was considered fungistatic because the activities of sclerotia and mycelia were resumed after placed in PDA medium without the compound(s). When the C. rosea culture filtrate was applied to tomato stem segments at different times, the size of the lesion caused by the pathogen reduced. The control efficiency was higher than 90% when the filtrate was applied either one day before or at the time of B. cinerea inoculation. In plants, the lesion length decreased by 50% when the filtrate was applied one day before the inoculation of the pathogen. According to the data, C. rosea isolates act by producing organic compound(s) that are deleterious, most likely through fungistasis, to B. cinerea.